Experimental confirmation of the cyclical concept of labor motivation in the financial sector activity - S. A. Shapiro; A. B. Veshkurova; N. G. Vishnevskaya (Путеводитель предпринимателя)
This article analyzes the results of the author’s research aimed at the confirmation of the hypothesis set out in the circular of the concept of motivation. The study was carried out among the employees of the financial sector of activity.